Identificação de problemas na produção de Pop Cork - Madhan, Sasi Kumar (2021)
The current context of the Europe, USA, China, India and worldwide industry is marked by an intense competition between producers to attract the customer´s choice. The dynamic needs of client feed the competitiveness to the companies, pushing them to lower prices, high quality and better delivery conditions in terms of lead time and quantities. The pop cork production makes more efficiency the production of larger amounts of granules in grain materials technology. Amorim cork industry is the biggest cork materials manufacturer company in the world and is located at Portugal, supplying to different fields such as aerospace, automobile industry, textiles and household things. Following this, innovation unit is embedded in the grain materials technology. This work expects to recognize the pop cork issues and to enhance the pop cork effectiveness by improving the cork expansion, as well as the equipment working conditions. The case study provides detailed information about the granules units 1 and 3, at na operational level. In the GMT (Granules Materials Technology) units 1 and 3, analyses and improvements in the cork expansion were carried out, by identifying the boilers capacity limitations, controls of the equipment conditions, operational failures and available resources, such as natural cork waste, because different kinds of Cork Bark are used in the pop cork production. These sections were analysed collecting samples of different kinds of cork bark used in the pop cork production, at diferente temperatures, observing as well the variation of cork expansion in order to identify the problems occurred in the process. Errors displayed by the equipment and/or pointed out by operators in the GMT units 1 and 3 were recorded. Corporate changes to promote the standardization of procedures, from initial objectives to evaluation, considering the planning, execution and reports, were also identified. At the end, the results of pop cork production in the GMT unit 1 and 3 were improved by 3%. Now, Amorim Cork Composites presents a more profitable process, which was proved. The regularity of maintenance operations should be undertaken to increase the granules production.